An Empirical Study of The Stock-Gilt Co-Movement in The UK Markets Using Copula Methods - Wu, Yuheng (Transactions on Economics, Business and Management Research, 2024)
Using a variety of copula models, this study examines the correlation and tail dependency between UK stock market and gilt market across three distinct economic periods: the financial crisis, the Covid-19 pandemic and normal economic period (normal time period in between financial crisis and Covid-19 pandemic without economic instability), and investigates how these correlations differ, with a particular focus on the extreme correlation. The analysis reveals that the UK stock market and gilt market are exhibiting certain correlations in all three time periods, but there’s significant variations in the strength of the correlations and tail dependencies.